Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography in Assessing Retroperitoneal Fibrosis: A Literature Review - Treglia, Giorgio (Hindawi Publishing Corporation, 2012)
Background and Purpose. Several studies have evaluated the role of fluorine-18-fluorodeoxyglucose positron emission tomography and positron emission tomography/computed tomography (FDG-PET and PET/CT) in diagnosing and assessing disease activity in patients with retroperitoneal fibrosis (RF). The aim of our paper is to perform a literature review on this topic. Methods. Scientific articles that evaluated the usefulness of FDG-PET and PET/CT in patients with RF were searched and discussed. Results. Eleven studies were found, and the main findings of these articles were described. Conclusion. FDG-PET and PET/CT are useful functional imaging methods for assessing patients with RF both in the diagnosis and in the treatment response evaluation. Moreover, further studies are needed to substantiate the role of FDG-PET and PET/CT in patients with RF.